DESIGN LANDSCAPE URBANISM PADA TAMAN HORTIKULTURA TROPIS WADUK PLUIT - Fransiska Lasriama; F. Tatang H Pangestu (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Plants are living things, plants can affect the lives of other living things, so it can be said that plants can affect an ecosystem. Horticulture is one of the most diverse types of plants in Indonesia, and can be grown in urban areas such as Jakarta. The ecology of horticultural plants must be studied to complement the urban landscape design of urban green open spaces and can also be consumed by the community. However, people's knowledge about horticultural plants that can be consumed is very lacking, especially the habits of urban people who tend to consume fast food, where this habit is actually not good for the body and the ecosystem. Therefore, we need a container that is able to revive and be able to develop horticultural plants that blend with the existing site conditions. Thus, the presence of an architectural container for growing horticultural crops does not damage the existing ecosystem conditions. The combination of ecological science, architectural technology, architectural methods, and technology for growing horticultural plants is expected to create an architectural container for horticultural plants to develop well and can attract people's interest to know several types of horticultural plants. Because knowledge and human health greatly affect the quality of an ecosystem. The horticulture that is planted is also a plant that can grow in the tropics, especially the selected site area, namely in North Jakarta. Thus, horticulture not only provides education to the public, but can grow, and fill urban public spaces, such as parks. Thus, a new ecosystem is created that is beneficial to fellow living things. Keywords: Ecology; Horticulture; Urbanism LandscapeAbstrakTumbuhan adalah makhluk hidup, tumbuhan dapat mempengaruhi kehidupan makhluk hidup lainnya, sehingga dapat dikatakan tumbuhan dapat mempengaruhi suatu ekosistem. Hortikultura merupakan salah satu jenis tanaman yang sangat beragam di Indonesia, dan dapat tumbuh di daerah perkotaan seperti Jakarta. Ekologi tanaman hortikultura harus dipelajari untuk melengkapi design landskap urbanisme ruang terbuka hijau kota dan juga dapat dikonsumsi oleh masyarakat. Namun, pengetahuan masyarakat tentang tanaman hortikultura yang bisa dikonsumsi sangat kurang, terutama kebiasaan masyarakat kota yang lebih cenderung mengkonsumsi makanan cepat saji, dimana kebiasaan ini sebenarnya tidak baik untuk tubuh dan ekosistem. Oleh karena itu, diperlukan suatu wadah yang mampu menghidupkan dan mampu mengembangkan tanaman hortikultura yang menyatu dengan kondisi tapak eksisting. Sehingga, kehadiran wadah arsitektur untuk menanam tanaman hortikultura tidak merusak kondisi ekosistem yang sudah ada. Perpaduan antara ilmu ekologi,  teknologi arsitektur, metode arsitektur, dan teknologi menanam tanaman hortikultura diharapkan dapat menciptakan wadah arsitektur untuk tanaman hortikultura berkembang baik dan dapat menarik minat masyarakat untuk mengenal beberapa jenis tanaman hortikultura. Sebab, pengetahuan dan kesehatan manusia pun sangat mempengaruhi kualitas suatu ekosistem. Hortikultura yang ditanam juga merupakan tanaman yang dapat tumbuh didaerah tropis, terutama daerah tapak terpilih, yaitu di Jakarta Utara. Dengan demikian, hortikultura tidak hanya memberikan edukasi kepada masyarakat, tetapi dapat tumbuh, dan mengisi ruang publik perkotaan, seperti taman. Sehingga, tercipta ekosistem baru yang bermanfaat bagi sesama makhluk hidup.